Stabilization of the limestone escarpment of the Skete of Osios Nikanoras under wet conditions due to future filling of the Ilarion dam's reservoir. - Mourtzas, N. D.; Gkiolas, A.; Kolaiti, E. (Bulletin of the Geological Society of Greece, 2013)
The Skete of Osios Nikanoras is located in a cavern of a vertical limestone escarpment 80m high, over Aliakmon River in West Macedonia. The vertical slope is structured predominantly of thick-bedded limestone, dipping moderately towards NW and only locally of thin-bedded limestone. It is crossed by three transverse and four normal faults. Rock mass was divided in sections, demarcated by bedding planes and major discontinuities. Each section was subdivided into rock blocks. Rock mass description was carried out in areas below the entrance level and the surrounding areas of the Skete as well. The future water level rise, due to the filling of the Ilarion Dam’s reservoir, followed by water level fluctuations, will impose an initial increase and a subsequent variation of water pressures in the rock mass discontinuities. The evaluation of the rock mass stability, due to water induced loads, was therefore required. Stability analysis has been performed in order to determine potential wedge, plane and toppling failure modes. The measures that were adopted for the conservation of the monument were designed taking into account the restrictions regarding the monuments preservation. The proposed solution comprised three stages of installation of support measures, namely, installation of temporary rock bolts for the pre-strengthening of the rock mass, followed by the execution of grouting and finally installation of permanent rock anchors, thus ensuring adequate factors of safety.